2016
DOI: 10.1007/s00442-016-3611-8
|View full text |Cite
|
Sign up to set email alerts
|

Plant species diversity affects soil–atmosphere fluxes of methane and nitrous oxide

Abstract: Plant diversity effects on ecosystem functioning can potentially interact with global climate by altering fluxes of the radiatively active trace gases nitrous oxide (N2O) and methane (CH4). We studied the effects of grassland species richness (1-16) in combination with application of fertilizer (nitrogen:phosphorus:potassium = 100:43.6:83 kg ha(-1) a(-1)) on N2O and CH4 fluxes in a long-term field experiment. Soil N2O emissions, measured over 2 years using static chambers, decreased with species richness unles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 54 publications
4
38
0
Order By: Relevance
“…, Hooper and Dukes ), where these effects could be related to increased N acquisition, increased N‐use efficiency, and reduced N losses (Niklaus et al. , , Scherer‐Lorenzen et al. , Fargione et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Hooper and Dukes ), where these effects could be related to increased N acquisition, increased N‐use efficiency, and reduced N losses (Niklaus et al. , , Scherer‐Lorenzen et al. , Fargione et al.…”
Section: Discussionmentioning
confidence: 99%
“…4d), probably because the litter layer (including mineral compounds) became too dry. Other studies (Adamsen and King, 1993;Karbin et al, 2016;Niklaus et al, 2016;Rosenkranz et al, 2006;) also showed that CH4 consumption is highest in the top centimeters of the mineral soil and that a decreasing soil water content is often associated with a higher CH4 consumption (Borken and Beese, 2006;Butterbach-Bahl et al, 2002;Hartmann et al, 2011). Stiehl-Braun et al (2011) observed that the most active zone of CH4 consumption shifted downward within the soil profile during a drought.…”
Section: Uncertainty In the Modeled Diffusivity Profile And Comparisomentioning
confidence: 91%
“…Similar as to our site, Borken & Beese [25] observed no effect of vegetation on N 2 O fluxes. Niklaus et al [55] observed that CH 4 uptake and soil N 2 O emissions decreased with plant species richness in a grassland experiment. They attributed the decrease in CH 4 uptake to an increase in soil water content.…”
Section: Spatial Variability Of Soil Gas Fluxesmentioning
confidence: 99%
“…High-affinity methanotrophic microbes are ubiquitous in aerated soil and specifically seem to live on the surface of aggregates and pores [54,55] that facilitate access to CH4. The rate of CH4 consumption is consequently limited, amongst other factors, by the supply of atmospheric CH4.…”
Section: Interaction Of Soil Physical Parameters Soil Gas Fluxes Anmentioning
confidence: 99%